2006
DOI: 10.1164/rccm.200507-1118oc
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin-releasing Peptide Receptor Antagonist Effects on an Animal Model of Sepsis

Abstract: We report that a selective GRP receptor antagonist attenuates the release of proinflammatory cytokines in vitro and in vivo and improves survival in "established" sepsis. These are consistent with the involvement of a new inflammatory pathway relevant to the development of sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 31 publications
7
47
0
Order By: Relevance
“…However, here we demonstrate the proinflammatory activity of the neuropeptide GRP. Our results also provide a unique candidate mechanism for the antiinflammatory effect of the GRPR antagonist RC-3095 in models of arthritis (9) and sepsis (10). We can also extend our model to explain the proinflammatory effect of GRP, because a GRP blocking agent effectively prevented asthma exacerbation in animal models (12).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, here we demonstrate the proinflammatory activity of the neuropeptide GRP. Our results also provide a unique candidate mechanism for the antiinflammatory effect of the GRPR antagonist RC-3095 in models of arthritis (9) and sepsis (10). We can also extend our model to explain the proinflammatory effect of GRP, because a GRP blocking agent effectively prevented asthma exacerbation in animal models (12).…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies revealed an antiinflammatory effect of RC-3095 in murine arthritis (9) and sepsis models (10). This effect was attributed to the inhibition of IL-1β and TNF-α production.…”
Section: Neutrophil Migration Toward Synovial Fluid (Sf) Of Rheumatoidmentioning
confidence: 89%
See 1 more Smart Citation
“…We have demonstrated that increased BLP levels in baboons with BPD are directly linked to oxidant exposure, because treatment of animals with a novel antioxidant abrogates these increased BLP levels (18,44). Similarly, GRP may have a role in acute lung injury (16,45). In view of the fact that BPD is a multifactorial disorder, it remains surprising that several characteristic histopathologic features of BPD can be induced by a single peptide in a simple newborn mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] More recently, it has been reported that releasing of GRP closely related to the progression and severity of chronic inflammatory diseases, including RA, and administration of GRPR antagonist have anti-inflammatory effects in inflammation models. 7,[10][11][12] RC-3095 is a synthetic polypeptide BN/GRP antagonist with the MW of Chemical and Pharmaceutical Bulletin Advance Publication 1106.32. Studies showed that RC-3095 could be an attractive and safe candidate compound for future trials in GRPR-related diseases, including specific types of cancer and chronic inflammatory diseases.…”
Section: Gastrin-releasing Peptide (Grp) Is the Mammalian Homologue Omentioning
confidence: 99%